Perceptual filters: Exploring disability and ableism’s cognitive framework - Abhimanyu Vasudeva; Palani Selvam Mohanraj; Richa Tripathi; Anita Kashi Shrivastava; Vikram Vardhan (Journal of Family Medicine and Primary Care)
Ableism, akin to other forms of discrimination such as sexism and racism, is increasingly recognized as a pervasive societal concern directed towards individuals with disabilities. This scholarly inquiry delineates the operational definition, manifestations, and ramifications of ableism, with a specific focus on its manifestations within healthcare settings. It underscores the critical need for targeted interventions aimed at mitigating biases among healthcare professionals and promoting inclusivity within healthcare delivery systems. Utilizing insights from cognitive psychology, the study conceptualizes ableism as a cognitive distortion, explicating the mechanisms through which biases shape perceptions and recommending Cognitive Behavioral Therapy (CBT) as a promising intervention modality. The paper advocates for exploration of intersectional analyses, utilization of qualitative research methodologies, and cultivation of collaborative partnerships with disability advocacy organizations to develop more comprehensive intervention approaches. Noteworthy limitations of the current discourse include the potential for tokenistic representations and the imperative for genuine and substantive engagement with the voices and experiences of individuals with disabilities.